Integrali elementarnih funkcij - Slapar, Marko (Obzornik za matematiko in fiziko, 2008)
It is a well known fact that certain integrals of elementary functions cannot be expressed in elemetary terms. An example of such an integral is ?$\int e^{x^2}dx$?. In this paper we show what is behind this theory and give some examples of elementary functions that do not have elementary integrals.
Keywords: algebra; analiza; elementarne funkcije; matematika